THE INFLUENCE OF HUMAN RESOURCE DEVELOPMENT ON EMPLOYEE PERFORMANCE THROUGH ORGANIZATIONAL CULTURE - Hefni Rastoma Arzain; Ana Sriekaningsih; Zuhad Ichyaudin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study focuses on testing the Influence of Human Resource Development on Employee Performance at PT. Eloda Mitra of Palembang Branch through organizational culture. The purpose of this study is to find out how the influence of human resource development on Employee Performance at PT Eloda Mitra of Palembang Branch through organizational culture. The sample used in this study was 40 employees. The sample collection technique in this study uses the saturated sampling method. The data analysis method in this study uses a quantitative analysis method using SmartPLS software. The test results show that, First, Human Resource Development has a positive effect on Organizational Culture. Second, Human Resource Development has a positive effect on employee performance. Third, Organizational Culture has a positive effect on Employee Performance. Fourth, Human Resource Development has an indirect effect on Employee Performance through Organizational Culture.Suggestions for PT Eloda Mitra of Palembang Branch to continue to maintain and continue to improve the work motivation of the workforce by continuing to provide a good position for the workforce, creating a mutually supportive work environment, developing creativity from the workforce so that the performance and productivity of the workforce.